Roles and responsibilities of expert clients in adolescent HIV service delivery in Eswatini: a conventional content analysis. Issue 1 (2nd January 2023) - Ahmed, Charisse V; Weissinger, Guy; Teitelman, Anne M; Dlamini, Ndumiso Sabelo; Dlamini, Nontsikelelo Patience; Dlamini, Thuthukile Cebsile; Nkambule, Angel; Nkambule, Siphesihle; Rice, Bridgette M; Calnan, Marianne
Abstract : We aimed to elucidate the specific roles and responsibilities of expert clients in service delivery among adolescents living with HIV in Eswatini, and to provide recommendations for enhancing adolescent service provision among expert clients and similar lay health workers throughout low- and middle-income countries. An exploratory qualitative descriptive methodology using conventional content analysis was used to meet our study aims. We recruited 20 expert clients and 12 key informants (programme managers, programme coordinators and nurses) to participate in semi-structured interviews, and we arranged four focus group discussions among adolescents living with HIV with seven to ten participants per focus group. Adherence counselling in clinical and community settings was considered paramount to the roles and responsibilities of expert clients with regard to adolescent-specific HIV service delivery. The following recommendations were made to enhance expert client service delivery practices among adolescents: (1) training in adolescent developmental, sexual and reproductive needs; (2) training to enhance clinical knowledge and skills; (3) additional work equipment and compensation; and d) more parent and guardian engagement in their work. While expert clients meet the needs of adolescents living with HIV in several capacities, they require additional resources, skills and training to improve their work, especially in the realm of sexual and reproductive health. Future research is needed to evaluate the impact of expert client service delivery on adolescent health outcomes.